2009
DOI: 10.3109/17453670903316793
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock waves enhance normal fibroblast proliferation in vitro and activate mRNA expression for TGF-β1 and for collagen types I and III

Abstract: Background and purpose Extracorporeal shock waves (ESWs) are used to good effect in the treatment of soft tissue injuries, but the underlying mechanisms are still unknown. We therefore determined the effects of ESWs on normal fibroblasts in vitro, in order to assess treatment-induced cell response.Methods A normal human fibroblast cell line (NHDF-12519) was treated with ESWs generated by a piezoelectric device (Piezoson 100; Richard Wolfe) using different protocols of impulses (300, 1,000, or 2,000 shots) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
54
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 24 publications
6
54
0
3
Order By: Relevance
“…However, the number of fibroblasts that migrated to the wound site increased notably after ESWT. This phenomenon was consistent with previous studies (Berta et al 2009;Kuo et al 2009b). Berta et al (2009) reported that application of ESW enhanced human dermal fibroblasts proliferation in vitro.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, the number of fibroblasts that migrated to the wound site increased notably after ESWT. This phenomenon was consistent with previous studies (Berta et al 2009;Kuo et al 2009b). Berta et al (2009) reported that application of ESW enhanced human dermal fibroblasts proliferation in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon was consistent with previous studies (Berta et al 2009;Kuo et al 2009b). Berta et al (2009) reported that application of ESW enhanced human dermal fibroblasts proliferation in vitro. Results from Kuo's study indicated that an appropriate dosage of ESWT could modulate fibroblasts recruitment, and thus, promote tissue remodeling in an ischemic skin flap rat model (Kuo et al 2009b).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Shockwaves are sonic pulses characterized by a high peak pressure (500mbar) short life cycle (10ms), fast pressure rise (<10ns), broad frequency spectrum (Hz) and the generation of stress forces upon interaction with interface Citation: Ottomann CMD, Antonic V, Münch S, Belfekroun C, [19,20], incisional wounds, and models of compromised wound healing such as diabetic wounds [21]. Investigations of mechanisms of action for the beneficial effects of ESWT led to reports of application of ESWT in vitro [22][23][24][25][26][27]. These studies indeed contributed toward improved understanding of biological effects of ESWT.…”
mentioning
confidence: 99%